Pengaruh Media Roda Keberuntungan Modifikasi terhadap Kemampuan Mengenal Angka di Taman Kanak-Kanak - Ayunda, Deartia; Yetti, Rivda; Yeni, Indra (Penerbit Aksara Rentaka Siar (ARS), 2019)
The purpose of the study was to find out the effect of Wheel of Fortune Media Modified on the Ability to Know Numbers in the Khaira Ummah Islamic Childhood Park in Padang. This type of research is quantitative with the quasy experiment method. The population of this study was Khaira Ummah Padang Islamic Kindergarten children, with the sampling technique being purposive sampling, namely group B6 for the experimental class and group B7 for the control class, each 12 children each. Data collection techniques using statement sheets, then the data is processed by different tests (t-test). Based on the data analysis, the average test results of the experimental group were 80.72 and SD was 7.84 while the control group was 72.91 and SD was 7.36. In testing the hypothesis obtained tcount of 2.4104 and ttable of 2.07387 at the real level Î± = 0.05 and dk = 22. Thus it can be concluded Media Wheel of Luck Modification increases in line with expectations in Khaira Islamic Kindergarten 2018/2019.